Transradial Access in Coronary Angiography: A Study of its Safety and Efficacy in Comparison to Transfemoral Access (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Coronary angiography is traditionally performed through transfemoral access. Transradial access is increasingly being used for this purpose for its various advantages. However, its use in Bangladesh is less well studied. The aim of this study was to find out the safety and efficacy of transradial access as compared to transfemoral access.Methods: This was a single-center, cross-sectional study. 100 randomly selected elective coronary angiography from August 2017 to September 2018 by the same operator using either transradial access or transfemoral access were analyzed.Results: Among 100 coronary angiography, transradial access were 50 and transfemoral access were 50. Fluoroscopy time was 3.08[1-9] vs 1.47 [1-17] minutes (p=.014), dose area product was 4807 [1947-11489] vs 3202 [1130-12826] ìGy.m2 (P